Unleashing the Power of Digital on Farms in Russia - and Seeking Opportunities for Small Farms - Nielson, David (World Bank, Washington, DC, 2018)
Rapidly emerging technologies that capture, manage, communicate, and use information in digital form are dramatically transforming the way that farming and agribusiness are done across the globe—especially for large commercial farms. Nowhere is this more true than in the Russian Federation, where many large agri-holding companies operate at the cutting edge of the application of digital technologies. These large industrial farms, with sizable land and livestock holdings, possess the financial resources and the management know-how to own and leverage the most advanced technology. Some have sophisticated information technology staff to develop and manage digital approaches to many aspects of farm operations. However, many of Russia’s farms—especially small and medium farms—lack the connectivity and skillsets needed to take advantage of such technologies. Many of these small farms also lack the equipment and the know-how to take advantage of the transformational digital opportunities from which they might profit. Yet the ever-expanding connectivity and availability of information and communication technology and digital tools could make it possible for transformational developments to happen on small, traditional, remote, and disadvantaged farms too.